Investigating the correlation of the number of diagnostic criteria to serum adiponectin, leptin, resistin, TNF-alpha, EGFR levels and abdominal adipose tissue. Issue 2 (April 2016) - Ayeser, Tayfun; Basak, Mesut; Arslan, Kadem; Sayan, Ismet
Abstract: Aim: Cardiovascular diseases are among the leading causes of morbidity and mortality in developed countries. Metabolic syndrome is a common clinical presentation posing significant risk in cardiovascular diseases. This study investigated the correlation between the number of diagnostic criteria and serum adiponectin, leptin, resistin, TNF-alpha, EGFR levels and abdominal adipose tissue in the individuals with metabolic syndrome. Materials and methods: This study included a total of 40 patients (18 men and 22 women) with metabolic syndrome that applied to the Internal Diseases Outpatient Clinic of Ümraniye Training and Research Hospital between March 2011 and August 2011. The data including age, gender, personal history, familial history, habits, height, weight, systolic blood pressure, diastolic blood pressure, body mass index, waist circumference, hip circumference, body composition (tanita) were recorded for each patient. Blood samples were collected for biochemical examinations. The serum adiponectin, leptin, resistin, TNF-alpha, EGFR levels were measured. Statistical analyses were carried out using the NCSS (Number Cruncher Statistical System) 2007 and the PASS (Power Analysis and Sample Size) 2008 Statistical Software (UT, USA). Results: When the patients with metabolic syndrome were analyzed by gender, no statistically significant difference was found between the EGFR and TNF-alpha levels ( p > 0.05). On the other side, the visceral fat rating and GGT levels of women were significantly lower than those of men ( p < 0.05). However, the resistin and leptin levels were found significantly higher in female patients as compared to male patients ( p < 0.05). Conclusion: In the present study, we did not observe any statistically significant change in abdominal adipose tissue thickness, serum TNF-alpha, adiponectin, resistin, and EGFR levels of the patients according to the number of diagnostic criteria; however, there was significant change in the patients' leptin levels.